Traditional African Art in Sub-Saharan Africa (Al-Farooq Journal of Sciences, 2026)
beyond aesthetic expression to include symbolic, functional, and social dimensions. It aims to analyze the formal and symbolic characteristics of this art within its historical and cultural contexts, focusing on key elements such as masks, sculptures, and materials used in artistic production.The research highlights the strong relationship between art, religious beliefs, and social rituals, emphasizing the collective and functional nature of artistic practices in traditional African societies.The study adopts a descriptive-analytical method supported by historical and anthropological approaches to interpret the deeper structure of African art and connect it to its socio-cultural context. It also discusses the impact of European colonialism and the interaction with modern global art on the transformation of this art’s functions and meanings.The study concludes that traditional African art represents a rich symbolic system reflecting the African worldview, demonstrating continuity and adaptability in the face of contemporary transformations.
Keywords: Traditional African Art – Sub-Saharan Africa – Symbolism – African Masks – Sculpture – Ritual Function – Cultural Structure – Art and Identity – Art Anthropology